Redesign of stone crushing plant system in Atlantic sand and gravel company / Sisavanh Suyavong - Sisavanh, Suyavong (2013)
The active aspect of stone crushing plant must be considered in order for process plants to achieve their goals and objectives in an efficient and cost effective manner. The key aspect of good crushing plant includes blasting and crushing process technology. In this study, the post-crushed quarrying plant processing and the expansion has been suggested. In the concept of Lean Production, inventory is considered as the waste of the firm, so in this study the focus will be on fulfilling the market demand, eliminate the excess product as well as inventory and get more profit. Optimal crushing production is obtained by designing the tertiary crushing system as the expansion production line of the current plant. After all components has been identified, especially, the material handling within the plant. The essential part which is the project economic analysis will take place to verify that the proposed product has the profitability and viability to process. Market demand analysis has been made, the tertiary crushing system and the 3D model has been designed, material and component usage has been selected, all cost and benefit have been identified. The result obtained has shown that the expansion is profitable to conduct. The break-even point was found to be in nine months of operation. The cost and benefit analysis has also been obtained while Net Present Value at 1,631 million kip (RM 652,400.00) of five years life cycle and Internal Rate of Return presents at 1.35. The overall crushing plant productivity improves to 0.99 percent and the manpower capacity improvement of 8.67 percent has been achieved.